Pilot Study of an Interprofessional Palliative Care Curriculum: Course Content and Participant-Reported Learning Gains. (March 2018) - Starks, Helene; Coats, Heather; Paganelli, Tia; Mauksch, Larry; van Schaik, Eileen; Lindhorst, Taryn; Hurd, Caroline; Doorenbos, Ardith
Context: The National Consensus Project for Quality Palliative Care Clinical Practice Guidelines recommend that palliative care clinicians work together as interprofessional teams. We created and piloted a 9-month curriculum that focused on 3 related domains: (1) patient-centered, narrative communication skills; (2) interprofessional team practice; and (3) metrics and systems integration. The multifaceted curriculum was delivered through 16 webinars, 8 online modules, 4 in-person workshops, reflective skill practice, written reflections, and small group online discussions. Objectives: Report evaluations of the course content and skill self-assessments from 24 interprofessional palliative care clinicians. Methods: Participants rated each learning activity and completed a retrospective pre–post test skill assessment. Learning gains were measured as the difference in the percentage of participants reporting "strong" or "highly competent" skill levels at baseline and the end of the course. Participants also provided examples of how they used the skills in practice. Results: Participants achieved an average learning gain of 50% across all domains, and in each domain communication (54%), interprofessional team practice (52%), and metrics and systems integration (34%). They also gave high ratings for the curriculum content (overall mean [standard deviation] rating of 5.5 (0.7) out of 6). Examples of practice impacts included improved skills in responding to emotions, understanding the equal importance of all professions on their team and incorporating different perspectives into their practice, and learning about outcome measurement in palliative care. Conclusion: This curriculum demonstrated success in increasing perceived skills for interprofessional palliative care clinicians in advanced communication, team practice, and metrics and system integration.